Development of mental health indicators at the district level in Madhya Pradesh, India: mixed methods study - Shalini Ahuja; Petra C. Gronholm; Rahul Shidhaye; Mark Jordans; Graham Thornicroft (BMC, 2018)
Abstract Background Strengthening routine information systems for mental health can augment scale up of community mental health services in India and other low- and middle-income countries. Currently little routine data is available in Indian settings. This study aimed to develop a core set of indicators for monitoring mental health care in primary health care settings Methods By using a sequential exploratory mixed methods design, key mental health indicators measuring service delivery and system performance were developed for the context of Madhya Pradesh, India. The research design involved a situation analysis, and conducting a prioritisation exercise and consultation workshops with key stakeholders. Results This study resulted in nine key mental health indicators covering both mental health service delivery indicators and mental health system indicators for Sehore district of Madhya Pradesh. Mean indicator priority scores ranging from 4.48 to 3.78 were reported. Conclusions This study demonstrated a phased approach to strengthen routine information systems for mental health at a primary care level in India. We recommend that similar research methods can be applied across comparable settings and these indicators can be adopted as a part of national routine information systems.